Human resource management - Mondy, R. Wayne 1940- (Allyn and Bacon, 1993)
Concentrating on the interrelationships among human resource management functions, this fifth edition features increased emphasis on multinational issues, a new section on total quality management and new coverage of how organizations respond to external environments.